Testing a Social Schematic Model of Police Procedural Justice - Nix, Justin (2018)
Procedural justice theory increasingly guides policing reforms in the United States and abroad. Yet the primary sources of perceived police procedural justice are still unclear. Building on social schema research, we posit civilians’ perceptions of police procedural justice only partly reflect their personal and vicarious experiences with officers. We theorize perceptions of the police are anchored in a broader “relational justice schema,” composed of views about how respectful, fair, and unbiased most people are in their dealings with others. Individuals’ experiences with certain nonlegal actors and neighborhood environments should directly affect their relational justice schema and indirectly affect their evaluation of police. Nevertheless, experiences with police, especially mistreatment by officers, should also affect perceived police procedural justice and may moderate the effects of relational justice schema endorsement. We test our hypotheses in two studies with national samples. The findings strongly support a social schematic model of perceived police procedural justice